Nonlinear Fowler-Nordheim behavior of a single SnO2 nanowire - Joshi, Padmashree D.; Joag, Dilip S.; Late, Dattatray J.; Mulla, Imtiaz S. (Journal of Vacuum Science & Technology B, 2017)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by a simple thermal evaporation method. The randomly oriented multiple nanowires grown by the vapor-liquid-solid mechanism exhibit low turn on field (0.8V/mu m defined for the current density of 1 mu A/cm(2)) and linear Fowler-Nordheim nature (FN). However, for the understanding of the nature of the FN plot, field emission behavior of a single SnO2 nanowire is investigated. The FN plot is observed to be nonlinear in nature. A simple model explaining the field emission mechanism from the semiconducting single SnO2 nanowire is proposed. (C) 2017 American Vacuum Society.